The Recovery Strategies Of Kampoeng Wisata Cinangneng In Facing The New Normal - Fitri Rismiyati (Program Studi Hospitality dan Pariwisata, 2021)
ABSTRACTIn 2020, the COVID-19 pandemic has come to Indonesia and has given some impacts on the entire tourism sector. One of them is the tourist attraction of Kampoeng Wisata Cinangneng. This study aims to find out the recovery strategies adopted by Kampoeng Wisata Cinangneng in dealing with the new normal. This study uses descriptive qualitative research methods with primary data collection techniques, including the in-depth interviews and supported by secondary data collection of documents.According to the results of research on managers and workers at Kampoeng Wisata Cinangneng, it is known that the COVID-19 pandemic has a significant impact on this tourist attraction. One of the impacts is the decreasing number of tourists visiting to Kampoeng Wisata Cinangneng, the lowest even up to 0 visit. This situation forced the management of Kampoeng Wisata Cinangneng to formulate a recovery strategy for the new normal. The strategy adopted by Kampoeng Wisata Cinangneng is to apply the CHSE health protocol in accordance with the Decree of the Minister of Health number HK.01.07/MENKES/382/2020 to workers, local people and tourists who come to visit. The strategy includes as making new tour packages in accordance with health protocols, making a new tourist attraction, and selling products made of plants in Kampoeng Wisata Cinangneng.Keywords: Kampoeng Wisata Cinangneng, COVID-19 Pandemic, Recovery Strategy, Tourism Sector